Measurement of High-Sensitivity Cardiac Troponin in Pulmonary Embolism: Useful Test or a Clinical Distraction - Lippi, Giuseppe; Favaloro, Emmanuel J.; Kavsak, Peter (Seminars in Thrombosis and Hemostasis, 2019)
The ability to predict death or other unfavorable outcomes after an acute pulmonary embolism (PE) is challenging, with current available risk score models having relatively unsatisfactory prognostic performance in this area. For example, the simplified pulmonary embolism severity index (sPESI), the most frequently used stratification tool, misclassifies a significant percentage of low- and high-risk patients. This gap in care, along with the increasing clinical availability of high-sensitivity cardiac troponin (hs-cTn) laboratory tests and the recent emphasis on detecting myocardial injury, may foster further evaluation of hs-cTn testing in patients with acute PE. Our analysis of the current scientific literature on hs-cTn in patients with acute PE identified that hs-cTn testing may provide valuable information for predicting future adverse outcomes and mortality, independently from baseline clinical risk assessment. Although the risk of an adverse event is indeed higher in patients with higher sPESI scores, cTns retain their prognostic value also in those at low risk, suggesting that a combination of hs-cTn with sPESI may provide an incremental value over assessment of either variable alone. Accordingly, the future development of updated risk stratification models, with the inclusion of laboratory tests such as hs-cTn, may represent an enhanced approach for risk stratification in patients with acute PE. Additional research, however, is needed to verify whether the combination of cTns, specifically as measured with hs-cTn assays, with other biomarkers may further improve the current capacity to efficiently manage patients with acute PE.
Keywords: pulmonary embolism; mortality; troponin; heart dysfunction; high sensitivity